2010
DOI: 10.1007/s10144-010-0203-z
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal and habitat cuing of Eurasian red squirrels in fragmented habitats

Abstract: Animal dispersal and subsequent settlement is a key process in the life history of many organisms, when individuals use demographic and environmental cues to target post-dispersal habitats where fitness will be highest. To investigate the hypothesis that environmental disturbance (habitat fragmentation) may alter these cues, we compared dispersal patterns of 60 red squirrels (Sciurus vulgaris) in three study sites that differ in habitat composition and fragmentation. We determined dispersal distances, pre-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 55 publications
5
49
0
Order By: Relevance
“…In our species, bequeathal of the natal home range does not occur . The direct observations of natal dispersal presented in this study confirmed our earlier conclusions (Wauters and Dhondt, 1993;Wauters et al, 1994Wauters et al, , 2010) that dispersal patterns of male and female Eurasian red squirrels are a conditional strategy, best explained by the degree of intra-sexual competition under local conditions.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…In our species, bequeathal of the natal home range does not occur . The direct observations of natal dispersal presented in this study confirmed our earlier conclusions (Wauters and Dhondt, 1993;Wauters et al, 1994Wauters et al, , 2010) that dispersal patterns of male and female Eurasian red squirrels are a conditional strategy, best explained by the degree of intra-sexual competition under local conditions.…”
supporting
confidence: 89%
“…Secondly, for 19 juveniles and subadults in SKW, natal patch was determined using maternity assignment in CERVUS 2.0 (Marshall et al, 1998). Details on DNA extraction, and microsatellite loci used for genotyping are given elsewhere (Trizizo et al, 2005;Wauters et al, 2010). Maternity was assigned at 95% and 80% confidence.…”
mentioning
confidence: 99%
“…Moderately intense forest harvest is not considered to be a threat because populations of red squirrels often remain viable in fragmented landscapes (Andrén and Delin 1994;Delin and Andrén 1999;Verbeylen et al 2003). Red squirrels are able to travel relatively long distances on open ground, thus are not as strongly affected by fragmentation as are other arboreal species (Wauters et al 2010;Mortelliti et al 2011). However, the amount of forest cover in the landscape is an important factor related to squirrels' presence (Mortelliti et al 2011) and red squirrels avoid clear-cuts (Hansson 1994).…”
Section: Eurasian Red Squirrelmentioning
confidence: 99%
“…Memory-based movements involve the use of acquired or 'genetic' information about movement locations. Navigation capacity can be disrupted when habitat quality decreases, habitat becomes fragmented and patches become isolated [41]. The perceptual range is a component of navigation capacity that relates to the distance over which animals can detect suitable areas of habitat (oriented movements).…”
Section: Navigation Capacitymentioning
confidence: 99%
“…[66]), can encourage individuals to remain in patches and reproduce, rather than dispersing into high mortality environments. However, dispersal is important for gene flow and metapopulation persistence, which can be driven by other internal factors, such as avoidance of competition or inbreeding [5,41]. Indeed, selection against dispersal in fragmented landscapes may be maladaptive in the long term if patch recolonization rates are reduced, thus compromising metapopulation viability [60].…”
Section: (A) Internal Statementioning
confidence: 99%